Cities, Regions and Transborder Mobility Along and Across the Border - Hardi, Tamás (Discussion Papers, 2012)
A decisive social experience of our current days is the increasing permeability of the internal borders of the European Union which, besides serving the integration of the economic and political macro-systems of the nation states is leading to the birth of an enlarging supranational economic and political space, in which the free flow of persons, labour, goods and capital are secured. Border regions play a specific role in this system. Will this cross-border flow pass them by, will they remain struggling peripheries of the nation states, or do they use, can they use the opportunities offered by their new situation? Is space opening up for them too? The question of our study is in what circumstances and to what extent the popula¬tion and economy of border regions can make use of the possibilities offered by the accessibility of the other side and if there is a chance for the birth of single cross-border regions. Borders and border areas are all unique, individual phenomena. The birth, change and character of the spatial borders depend to a large extent on the spatial unit (in this case: state) they surround, but this is a mutual relationship: states, border regions, and the characteristics of the state border all influence each other. This is why it is not enough to analyse the political, social, eco-nomic and cultural features of the border regions via the comparison of case studies; we have to strive for the generalisation of the deeper lying reasons, placing them into a theoretical and historical context.